Twenty-first century political justice: Reflections on the blind spots of current debates on penality - Brandariz García, José Ángel (Crime, law and social change, 2023)
This paper aims to examine the contours of current manifestations of political justice, in a time in which liberal democracy arrangements are more widespread than ever before. For these purposes, it begins by exploring international indices unveiling varying degrees of illiberal penal practices in global north jurisdictions. Subsequently, it scrutinises the Spanish penal field, in which outmoded political justice practices are intriguingly enduring and have been apparently on the rise over the last decade. In analysing the political catalysts of these Spanish cases, the paper sheds light on certain factors nurturing twenty-first century forms of political justice and enemy penology. Finally, the paper concludes by outlining a research agenda for seriously considering these ‘abnormal justice’ phenomena in current academic conversations on penality.